1990
DOI: 10.1111/j.1749-7345.1990.tb00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Eyestalk‐AblatedPenaeus stylirostrisFed Various Levels of Total Dietary Lipid

Abstract: Effects of total dietary lipid (TDL) on reproduction of Penaeus srylirostris were compared using a series of diets ranging from 7.8% to 13.9% TDL. In addition, a commercial feed was compared to the experimental feeds, and a single fresh diet component (squid as 40% of diet) was compared to a multiple fresh component portion (squid, bloodworms, shrimp, and brine shrimp as 40% of diet). The control diet consisted of the four fresh components in equal proportions. Significant differences among diet treatments dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 20 publications
6
73
0
5
Order By: Relevance
“…broodstock by Bray et al 1990b . These authors conducted a reproduction trial with Litopenaeus stylirostris fed three different total lipid levels: 7.8%, 11.1% and 13.9%.…”
Section: Total Lipidsmentioning
confidence: 99%
“…broodstock by Bray et al 1990b . These authors conducted a reproduction trial with Litopenaeus stylirostris fed three different total lipid levels: 7.8%, 11.1% and 13.9%.…”
Section: Total Lipidsmentioning
confidence: 99%
“…In several studies, poor reproductive performance or low offspring quality was observed when suboptimal broodstock Ž . diets were used Chamberlain, 1988;Bray et al, 1990;Cahu et al, 1995 . The challenge is to increase our knowledge of broodstock nutrition so that large-scale commercial production of high quality nauplii can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…The marine alga, Enteromorpha sp. supplementation has also been reported for better growth performance and FCR in Penaeus monodon, Penaeus indicus, Papeneopsis stylirostris, L. vennamei and M. rosenbergii (Bray et al, 1990). Sunitha and Rao (2003) have reported better weight gain in Tilipia mossambica when fed with blue green algae (Chlorella, Anabaena, Oscillatoria, Nostoc).…”
Section: Discussionmentioning
confidence: 93%